Sex specific differences in fetal middle cerebral artery and umbilical venous doppler - Prior,T; Wild,M; Mullins,E; Bennett,P; Kumar,S (PLoS One, 2013)
BackgroundThe incidence of several adverse pregnancy outcomes including fetal growth restriction are higher in pregnancies where the fetus is male, leading to suggestions that placental insufficiency is more common in these fetuses. Placental insufficiency associated with fetal growth restriction may be identified by multi-vessel Doppler assessment, but little evidence exists regarding sex specific differences in these Doppler indices or placental function. This study aims to investigate sex specific differences in fetal and placental perfusion and to correlate these changes with intra-partum outcome.Methods and FindingsThis is a prospective cohort study. We measured Doppler indices of 388 term pregnancies immediately prior to the onset of active labour (≤3 cm dilatation). Fetal sex was unknown at the time of the ultrasound assessment. Information from the ultrasound scan was not made available to clinical staff. Case notes and electronic records were reviewed following delivery. We report significantly lower Middle Cerebral artery pulsatility index (1.34 vs. 1.43, p=0.004), Middle Cerebral artery peak velocity (53.47 cm/s vs. 58.10 cm/s, p=<0.001), and Umbilical venous flow/kg (56 ml/min/kg vs. 61 ml/min/kg, p=0.02) in male fetuses. These differences however, were not associated with significant differences in intra-partum outcome.ConclusionSex specific differences in feto-placental perfusion indices exist. Whilst the physiological relevance of these is currently unknown, the identification of these differences adds to our knowledge of the physiology of male and female fetuses in utero. A number of disease processes have now been shown to have an association with changes in fetal haemodynamics in-utero, as well as having a sex bias, making further investigation of the sex specific differences present during fetal life important. Whilst the clinical application of these findings is currently limited, the results from this study do provide further insight